Health risks associated with the use of wastewater and excreta in agriculture in northern Vietnam - Phuc Pham Duc; Hung Nguyen-Viet; Zurbrugg, C.; Zinsstag, Jakob; Cam Dac Phung; Hattendorf, J.; Odermatt, P. (2012)
We studied the health risks related to wastewater and excreta reuse in an agricultural community in northern Vietnam, with a focus on intestinal parasitic infections and diarrhoeal diseases. Several epidemiological studies were conducted to assess the relative importance of exposure to wastewater and excreta for parasitic infection and diarrhoeal episodes in Hanam province. Exposure data were obtained from household and individual interviews. Stool examinations were used to assess infection status. Quantitative microbial risk assessment (QMRA) of Escherichia coli, Giardia lamblia, and Cryptosporidium parvum infection due to exposure to wastewater and excreta was conducted to estimate diarrhoeal risks in the environmental sanitation and agricultural systems. Helminth infections were prevalent (Ascaris lumbricoides 24%, Trichuris trichiura 40%, and any helminth infections 47%). Risk of helminth infection increased for people having direct contact with Nhue River water, as well as for people using human excreta as fertiliser. Tap water use in households proved to be a protective factor against T. trichiura infection. Diarrhoeal incidence in adults was 0.28 episodes per person per year (pppy). Direct contact with water from the Nhue River and local ponds, handling practices of human excreta, and use of animal excreta as fertilisers were important risk factors for diarrhoeal diseases. Inadequate use of protective measures, never or rarely washing one’s hands with soap, and having eaten raw vegetables the day before were also associated with increased the risks of diarrhoea. QMRA revealed that the most hazardous exposures included direct contact with the Nhue River, local pond and field water, household sewage, and composted excreta. The annual diarrhoeal risks were much greater than the WHO threshold values of 10 -3 pppy. Thus, important health impacts were documented in agricultural settings where wastewater and excreta are commonly used. Mitigation efforts must address personal hygiene practices and safe water and food consumption.